ChemInform Abstract: Photoinduced Nonlinear Optical Effects in Nd‐Doped δ‐BiB3O6 Crystals. Issue 34 (26th August 2014) - Majchrowski, A.; Wojciechowski, A.; Kityk, I. V.; Chrunik, M.; Jaroszewicz, L. R.; Michalski, E.
Abstract Second harmonic generation, Pockels effect, and piezoelectricity are investigated on Nd‐doped δ‐BiB3O6 crystals obtained below 680 °C from stoichiometric BiB3O6 melt containing 1 at.% Nd3+ ions.